Lutein and zeaxanthin reduce neuronal cell damage caused by lipid peroxidation - Satoshi Morita; Toshiaki Sueyasu; Hisanori Tokuda; Yoshihisa Kaneda; Takayuki Izumo; Yoshihiro Nakao (Biochemistry and Biophysics Reports)
Oxidative stress and lipid peroxide levels in the brain increase with aging. The carotenoids lutein and zeaxanthin have potent antioxidant properties and the ability to improve cognitive function. However, their effects on neuronal damage via lipid peroxidation remain unknown. Therefore, we aimed to elucidate the effects of these carotenoids on neuronal damage induced by accumulated peroxidized lipids. We developed an oxidative stress model of lipid peroxidation-induced neuronal damage using differentiated neuronal cells derived from human neuroblastoma SH-SY5Y cells in vitro. Combining rotenone and RSL3 increased mitochondrial oxidative stress and lipid reactive oxygen species (ROS), which resulted in enhanced neuronal damage. Lutein and zeaxanthin were added to the cells for 1 week, and these carotenoids suppressed mitochondrial oxidative stress and lipid peroxidation in differentiated neuronal cells and mitigated neuronal damage. Further investigation is required to clarify the underlying pathways in detail.